Penerapan Teori Struktural dalam Penyusunan Kurikulum Berbasis Kompetensi - Mahdi Bahar (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
As an entity, curriculum contains elements having interrelated functions which systemically move toward the achievement of its goals. Therefore, a curriculum should be developed under Structural Theory, which highlights organism principles whereby the achievement of organization goals is dependent on the participation of all the elements. This article presents practical illustrations of how to develop a curriculum utilizing the Structural Theory.